Five key factors for success at the Beijing Winter Olympics - Sandbakk, Ø. (HIIT Science, 2022)
From the author's point of view the five key factors for success at the Beijing Winter Olympics are: 1) Hypoxic training: Yes! But don`t forget altitude acclimatization 2) Be warmed up to face the cold 3) Prepare to face the jet lag 4) Covid issues still remain 5) Teamwork makes the dream work!